PROBLEMS OF LEGAL REGULATION OF PRIVATIZATION OF LAND PLOTS THROUGH ELECTRONIC ONLINE-AUCTION - Raxmatillaev Jasurbek Raxmatilla og‘li (American Journals, 2023)
In this article, in the privatization of non-agricultural land plots, auctions, Internet auctions, e-commerce platform, implementation of entrepreneurship and urban development activities, Evaluation activities, Categories of land plots to be privatized, vacant land plots, agricultural lands owned by local government bodies, problems of state real estate objects are revealed.
Keywords: non-agricultural land plot, privatization, electronic trade, categories of land plots, real estate objects.